Political Uncertainty and Its Impact on Economic Confidence in Thailand: An Analysis of the Political Situation, 2025–2026 - Malaikul, Lada (Thai Social Science Journal, 2026)
This article aims to analyze the relationship between political uncertainty and economic confidence in Thailand, focusing on the political dynamics during 2025–2026. During this period, Thailand experienced significant political fluctuations arising from political competition, conflicts among political parties, and the influential role of independent institutions and the Constitutional Court in supervising and balancing state power. The findings indicate that political uncertainty affects the economy through several channels, including declining investor confidence, delays in private investment, volatility in financial markets, and uncertainty regarding economic policy directions. Moreover, conflicts within coalition governments and political disputes can lead to delays or inconsistencies in economic policy implementation, thereby undermining the government's capacity to promote long-term economic development. Comparative analysis with other Asian economies such as South Korea, Indonesia, and Taiwan demonstrates that although these countries experience intense political competition, strong political institutions and consistent economic policies help maintain economic confidence and stability. The article argues that strengthening Thailand’s economic stability requires parallel efforts to improve political institutions and ensure policy stability. Key policy recommendations include establishing long-term economic policy frameworks, reducing institutional conflicts within the political system, and enhancing transparency in government policymaking. These measures can help reduce policy uncertainty and strengthen investor confidence, which are essential factors for sustaining economic development in the long run.